Posterior staphylomas in eyes with retinitis pigmentosa without high myopia - Xu, Xian; Jonas, Jost B. (Retina, 2019)
Purpose: To describe features of posterior staphylomas in nonhighly myopic eyes with retinitis pigmentosa (RP). - Methods: The retrospective observational case series study included patients with RP and an axial length of <26.5 mm and searched for eyes with posterior staphylomas. All study participants underwent fundus photography and optical coherence tomography. - Results: The study identified 13 eyes of 7 patients with a narrow macular staphyloma. Mean age was 40.9 ± 17.9 years (range 9-62 years) and mean axial length was 24.90 ± 0.69 mm. The staphyloma edges corresponded to the margin between the retinal atrophic area in the fundus midperiphery and the relatively unaffected fundus center. On vertically orientated optical coherence tomography images, the staphyloma edges showed a slight inward protrusion of the sclera and a ring-like localized choroidal thinning with choroidal rethickening in direction toward the fovea and toward the periphery of the fundus. The upper and lower staphyloma edges did not differ in steepness. The thickness of the subfoveal choroid (138.6 m ± 50.1 µm) was thinner than the normal range after adjusting for age and axial length in all eyes. Two eyes with advanced RP in the macula showed a subfoveal choroidal thickness of 95 µm and 88 µm. - Conclusion: Narrow macular staphylomas can occur in nonhighly myopic eyes with RP and, in contrast to staphylomas in highly myopic eyes, show a less marked thinning of the subfoveal choroid. The occurrence of posterior staphylomas in nonhighly myopic eyes with RP may provide hints to unravel the etiology of posterior staphyloma formation.